Pengaruh Program Tayangan Hafidz Indonesia Di RCTI Terhadap Motivasi Belajar Al - Qur'an (Survei Pada Siswa SDN 06 Sawangan Baru, Depok) - Muhammad Faiz; Mulkan Habibi (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
In modern times, technology is becoming more sophisticated. Similar to television, only a few television programs have educational components; therefore, in this situation, parental involvement is crucial to prevent these harmful effects. This study aims to ascertain how the Indonesian Hafidz Program on RCTI affects students at SDN 06 Sawangan Baru in Depok's desire to learn the Al-Qur'an. utilizing survey techniques and a quantitative approach. 100 students from SDN 06 Sawangan Baru in Depok made up the population in this study. Utilizing saturated samples is the sampling method. A questionnaire is used to collect the data, and simple linear regression analysis is used to analyze the results. The study's findings demonstrate that the calculated t value (12.219) exceeds the t table (1.984), and that H0 follows.